Adequate incision and proper drainage gives better outcome in cellulitis patients - Bagree, Rajendra; Gupta, Ayush; Kumar, Ritesh; Srinivas, Vinay; Kumar, Nitish; Kumar, Naveen (International Surgery Journal, 2024)
Background: We assessed the outcome of adequate incision and proper drainage of toxic fluid in the management of cellulitis patients in addition to the standard conservative approach of limb elevation, immobilisation and use of antibiotics. Methods: We conducted a retrospective cohort study in 150 patients of both sexes of age group 15-75 years admitted with cellulitis undergoing incision and drainage as an emergency procedure. Aetiologies, comorbidities and changes in levels of total leucocyte count, urea and creatinine were checked preoperatively and after surgical drainage. Management of the incision site and ulcer was done on follow up after the initial toxaemia resolved. Results: One hundred fifty patients including 98 males and 52 females of age group 15-75 years were included in this study. The most common site of cellulitis was found to be lower limb in 69 followed by upper limb in 40 cases. The aetiology was mostly traumatic in 68 patients followed by diabetes in 40 cases. Incision and drainage were performed in 108 cases and 42 cases needed debridement. Reduction in the total counts and improvement in the renal functions were seen in the patients. Upon follow up the patients presented with a healed ulcer with granulation tissue at base 68 of which were managed using SSG and 35 needed secondary suturing. There was no mortality seen in the study although 10 patients had to undergo further debridement and 2 patients needed a lower limb amputation. Conclusions: Cellulitis is one of the most commonly encountered pathologies in the outpatient department and is often managed conservatively. Extensive spread and complications can lead the patient to land in sepsis and multiorgan dysfunction. Thus, adequate incision and proper drainage of toxic fluids can prevent such complications and give better outcome for the patient.